Methylglyoxal attenuates insulin signaling and downregulates the enzymes involved in cholesterol biosynthesis - Deshmukh, Arati B.; Bai, Shakuntala; Aarthy, T.; Kazi, Rubina S.; Banarjee, Reema; Rathore, Rajeshwari; Vijayakumar, M. V.; H. V. Thulasiram; Bhat, Manoj Kumar; Kulkarni, Mahesh J. (Molecular Biosystems, 2017)
Methylglyoxal (MG) is a highly reactive dicarbonyl known to be elevated under the hyperglycemic conditions of diabetes and is implicated in the development of diabetic complications. Therefore, the current study investigates the role of MG in exacerbating insulin resistance at the insulin signaling level, as well as its effect on the global proteomic level. By using insulin sensitive rat muscle cells (L6) and Chinese hamster ovary (CHO) cells stably expressing the insulin receptor (IR) and a glucose transporter fused with green fluorescent protein (GLUT4-GFP), we have observed that MG impairs insulin signaling, inhibits GLUT4 translocation and reduces glucose uptake. SWATH MS analysis, a label-free quantitative mass spectrometric approach, showed altered expression of 99 proteins out of 2404 identified in response to MG treatment. These proteins are mainly involved in stress response, protein folding and proteolysis. Some of the deregulated proteins such as thioredoxin 2, glutathione S transferase, T complex protein 1 subunit beta (tcbp1), heat shock protein 90 and E3 ubiquitin ligase were previously reported to be associated with either diabetes or insulin resistance. Interestingly, aminoguanidine (AMG), a potent dicarbonyl scavenger, restored the deleterious effects of MG. For the first time, we report that MG induces downregulation of enzymes involved in cholesterol biosynthesis such as acetyl-CoA acetyltransferase, hydroxymethylglutaryl-CoA synthase, farnesyl pyrophosphate synthetase, squalene monooxygenase, and lanosterol synthase. GC MS analysis for sterol metabolites corroborated the proteomic results; MG significantly reduced cholesterol production whereas AMG treatment restored cholesterol production to levels similar to the control. Thus, MG leads to primary defects in insulin signaling and cellular abnormalities at the proteomic and metabolic levels, both of which may contribute to the development of insulin resistance.

Development of multiple reaction monitoring assay for quantification of carnosine in human plasma - Pandya, Vaibhav Kumar; Sonwane, Babasaheb; Rathore, Rajeshwari; Unnikrishnan, A. G.; Kumaran, Sangaralingam; Kulkarni, Mahesh J. (RSC Advances, 2020)
Carnosine, a histidine containing dipeptide, exerts beneficial effects by scavenging reactive carbonyl compounds (RCCs) that are implicated in pathogenesis of diabetes. However, the reduced carnosine levels may aggravate the severity of diabetes. The precise quantification of carnosine levels may serve as an indicator of pathophysiological state of diabetes. Therefore, we have developed a highly sensitive targeted multiple reaction monitoring (MRM) method for quantification of carnosine in human plasma samples. Various mass spectrometry parameters such as ionization of precursor, fragment abundance and stability, collision energy, tube lens offset voltage were optimized to develop a sensitive and robust assay. Using the optimized MRM assay, the lower limit of detection (LOD) and limit of quantification (LOQ) for carnosine were found to be 0.4 nM and 1.0 nM respectively. Standard curves were constructed ranging from 1.0 nM to 15.0 mu M and the levels of carnosine in mice and human plasma were determined. Further, the MRM assay was extended to study carnosine hydrolyzing activity of human carnosinases, the serum carnosinase (CN1) and the cytosolic carnosinase (CN2). CN1 showed three folds higher activity than CN2. The MRM assay developed in this study is highly sensitive and can be used for basal plasma carnosine quantification, which can be developed as a novel marker for scavenging of RCCs in diabetes.

Mechanistic insights on anserine hydrolyzing activities of human carnosinases - Pandya, Vaibhav Kumar; Shankar, S. Shiva; Rajesh, S.; Rathore, Rajeshwari; Kumaran, Sangaralingam; Kulkarni, Mahesh J. (Biochemica ET Biophysica Acta- General Subjects, 2023)
Anserine and carnosine represent histidine-containing dipeptides that exert a pluripotent protective effect on human physiology. Anserine is known to protect against oxidative stress in diabetes and cardiovascular diseases. Human carnosinases (CN1 and CN2) are dipeptidases involved in the homeostasis of carnosine. In poikilothermic vertebrates, the anserinase enzyme is responsible for hydrolyzing anserine. However, there is no specific anserine hydrolyzing enzyme present in humans. In this study, we have systematically investigated the anserine hydrolyzing activity of human CN1 and CN2. A targeted multiple reaction monitoring (MRM) based approach was employed for studying the enzyme kinetics of CN1 and CN2 using carnosine and anserine as substrates. Surprisingly, both CN1 and CN2 can hydrolyze anserine effectively. The observed catalytic turnover rate (Vmax/[E]t) was 21.6 s-1 and 2.8 s-1 for CN1 and CN2, respectively. CN1 is almost eight-fold more efficient in hydrolyzing anserine compared to CN2, which is comparable to the efficiency of the carnosine hydrolyzing activity of CN2. The Michaelis constant (Km) value for CN1 (1.96 mM) is almost three-fold lower compared to CN2 (6.33 mM), representing higher substrate affinity for anserine-CN1 interactions. Molecular docking studies showed that anserine binds at the catalytic site of the carnosinases with an affinity similar to carnosine. Overall, the present study elucidated the inherent promiscuity of human carnosinases in hydrolyzing anserine using a sensitive LCMS/MS approach.
Keywords: Anserine; Carnosinase; Carnosine; Diabetes; LC-MS; MS; Multiple reaction monitoring (MRM); Promiscuity